2015
DOI: 10.1136/bmjopen-2014-007195
|View full text |Cite
|
Sign up to set email alerts
|

Validating prediction scales of type 2 diabetes mellitus in Spain: the SPREDIA-2 population-based prospective cohort study protocol

Abstract: IntroductionThe incidence of type 2 diabetes mellitus (T2DM) is increasing worldwide. When diagnosed, many patients already have organ damage or advance subclinical atherosclerosis. An early diagnosis could allow the implementation of lifestyle changes and treatment options aimed at delaying the progression of the disease and to avoid cardiovascular complications. Different scores for identifying undiagnosed diabetes have been reported, however, their performance in populations of southern Europe has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 59 publications
1
11
0
5
Order By: Relevance
“…This study was conducted as part of a broader project, the S creening PRE -diabetes and type 2 DIA betes (SPREDIA-2) study, which has been described in detail elsewhere [ 16 ]. SPREDIA-2 is a population-based prospective cohort study in which baseline screening was performed from July 2010 to March 2014 according to Standards for Reporting of Diagnostic Accuracy criteria [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted as part of a broader project, the S creening PRE -diabetes and type 2 DIA betes (SPREDIA-2) study, which has been described in detail elsewhere [ 16 ]. SPREDIA-2 is a population-based prospective cohort study in which baseline screening was performed from July 2010 to March 2014 according to Standards for Reporting of Diagnostic Accuracy criteria [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted as part of a broader project, the S creening PRE -diabetes and type 2 DIA betes (SPREDIA-2) study, which has been described in detail elsewhere [ 23 ]. SPREDIA-2 is a population-based prospective cohort study in which baseline screening was performed from July 2010 to March 2014.…”
Section: Methodsmentioning
confidence: 99%
“…However, subjects in the participants group had a significantly greater family history of DM, hypertension and dyslipidemia compared with the non-participants group ( S1 Table ). The study procedure has been described in detail elsewhere [ 23 ]. Briefly, recruitment was divided into three phases.…”
Section: Methodsmentioning
confidence: 99%
“…age over 45 years, history of gestational diabetes, family history of diabetes or obesity). Salinero-Fort and colleagues reported that there was no consensus on the selection of the optimal high-risk subgroups or on how regularly these screens should be performed (Salinero-Fort et al, 2015). As a consequence, risk scores have been developed in order to better identify high risk participants.…”
Section: Screening Tests For Diabetesmentioning
confidence: 99%